Excavations at Rangpur and other Explorations in Gujarat - Rao, S. R. (1962)
with contributions by В. В. Lal, Bhola Nath, S. S. Gosh, and Krishna Lal; vgl. besonders 180-181: Foreign Trade between Lothal and West-Asian Cities... and Baḥrain.